Impact of the COVID-19 Outbreak on Anesthesiologist Assistance for Endoscopic Procedures - Calcedonio Calcara; Camilla Ciscato; Arnaldo Amato; Emanuele Sinagra; Costanza Alvisi; Sandro Ardizzone; Andrea Anderloni; Pietro Gambitta (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims: The coronavirus disease 2019 (COVID-19) outbreak has modified the activities of endoscopy units worldwide. Herein, we investigated the impact of the COVID-19 outbreak on anesthesiologist assistance for endoscopic procedures in Lombardy, Italy. Methods: A questionnaire concerning anesthesiologist assistance provided from October 26 to December 6, 2020, in comparison with the same period in 2019, was sent to endoscopic units in Lombardy. Results: Approximately 54% (34/63) of the units responded. A reduction in the number of all endoscopies (-33.5%; 18792 in 2020 vs. 28264 in 2019) and anesthesiologist-assisted endoscopies (-15.3%; 2652 in 2020 vs. 3132 in 2019) was reported. A greater reduction in anesthesiologist assistance was observed in government community units (-29.5%) than in academic (-14%) and private community units (-4.6%). Among all units, 85% reported a reduction in anesthesiologist assistance; 65% observed a delay/cancellation of procedures; 59%, a restricted patient selection; 17%, the need to transfer some patients to other hospitals; and 32%, a related worsening of procedure quality. Conclusion: The COVID-19 pandemic compromised the anesthesiologist assistance for endoscopic procedures in Lombardy, which worsened the procedure quality mainly in government community units. The COVID-19 "stress test" suggests a more balanced allocation of anesthesiologic resources in the future.